Implikasi Pemahaman Tritunggal terhadap Perbedaan Pandangan tentang Misi - Tony Salurante; Dewi Yuliana; Moses Wibowo; Jonidius Illu (Sekolah Tinggi Teologi Baptis, Jakarta, 2021)
The correct understanding of the doctrine of the Trinity plays an important role in the theology and praxis of believers. Unfortunately, these implications have not yet appeared in the church’s mission in which every believer is called to proclaim and live the truth of God – something that cannot be separated from deeds and words. Not just thinking about the concept of going out to send. This article is an integrative effort that has been started by Lesslie Newbigin and David Bosch to change the paradigm of a church mission in the world. This article shows the relation between the concept of Trinitarian and mission. With this attempt, the church will be able to play a significant role contextually without losing the important values of the Bible.AbstrakPemahaman yang benar tentang Tritunggal memiliki signifikansi besar dalam teologi dan kehidupan praxis orang percaya. Sayangnya implikasi tersebut belum nampak dalam misi gereja yang didalamnya setiap orang percaya terpanggil untuk menyatakan dan menghidupi kebenaran Allah. Penelitian ini adalah sebuah usaha integratif untuk menunjukkan apa yang telah dimulai Lesslie Newbigin maupun David Bosch untuk merubah paradigma misi gereja di dunia. Dengan cara gereja melihat sebuah misi dari perspektif ajaran Tritunggal gereja akan mampu bersaksi dengan kontekstual tanpa harus kehilangan nilai biblikal yang penting dari Alkitab.